Cerebrovascular Manifestations of Neurosarcoidosis: An Underrecognized Aspect of the Imaging Spectrum - Bathla, G.; Watal, P.; Gupta, S.; Nagpal, P.; Mohan, S.; Moritani, T. (American Journal of Neuroradiology, 2018)
SUMMARY: Involvement of the central nervous system by sarcoidosis, also referred to as neurosarcoidosis, is seen clinically in about 5% of patients with systemic disease. CNS involvement most frequently affects the leptomeninges and cranial nerves, though the ventricular system, brain parenchyma, and pachymeninges may also be involved. Even though the involvement of the intracranial vascular structures is well-known on postmortem studies, there is scant literature on imaging manifestations secondary to the vessel wall involvement, being confined mostly to isolated case reports and small series. The authors present a review of various cerebrovascular manifestations of neurosarcoidosis, along with a brief synopsis of the existing literature.ICHintracerebral hemorrhageNSneurosarcoidosis